MANAJEMEN HUMAS UNTUK PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH KEJURUAN (SMK) - Sunarto; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Public Relations has a strategic role in efforts to improve the quality of educational institutions. With the existence of public relations, it is hoped that mutual understanding will occur, as a result, it will lead to a good attitude of cooperation between the community and the school to overcome educational problems faced by both parties. programs held in educational institutions. In addition, the implementation of public relations management at educational institutions that are communication links or extensions of information to be conveyed to the public, strives for the information to be conveyed to the public quickly and accurately. However, there are often challenges or obstacles in the field of public relations, such as in terms of coordination patterns, institutions, HR competencies, infrastructure, and the lack of commitment from top leaders.